2021
DOI: 10.1002/hep.32062
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1β‐Induced Elevation of Solute Carrier Family 7 Member 11 Promotes Hepatocellular Carcinoma Metastasis Through Up‐regulating Programmed Death Ligand 1 and Colony‐Stimulating Factor 1

Abstract: Background and Aims Because of a paucity of effective treatment options, metastasis is still a major cause for HCC‐associated mortality. The molecular mechanism of inflammation‐induced HCC metastasis is open for study. Here, we characterized the function of solute carrier family 7 member 11 (SLC7A11) in inflammation‐related HCC metastasis and probed therapy strategies for this subpopulation of patients. Approach and Results Elevated expression of SLC7A11 was positively correlated with poor tumor differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 50 publications
(65 reference statements)
0
59
0
Order By: Relevance
“…The expression of PD-L1 was mediated via the nuclear factor-kappa B (NF-kB) signaling pathway, which was activated by the reduction in GSH levels [42]. Upregulated SLC7A11 promoted the expression of PD-L1 and CSF1 through the αKG/HIF1α axis, which further recruited TAMs and MDSCs infiltration [43]. These results suggested that targeting these regulators may provide a way in which to reverse the cold immune microenvironment and enhance the antitumor effects.…”
Section: Discussionmentioning
confidence: 95%
“…The expression of PD-L1 was mediated via the nuclear factor-kappa B (NF-kB) signaling pathway, which was activated by the reduction in GSH levels [42]. Upregulated SLC7A11 promoted the expression of PD-L1 and CSF1 through the αKG/HIF1α axis, which further recruited TAMs and MDSCs infiltration [43]. These results suggested that targeting these regulators may provide a way in which to reverse the cold immune microenvironment and enhance the antitumor effects.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that the upregulation of SLC7A11 is associated with poor prognosis of HCC, while the downregulation of SLC7A11 can inhibit the growth of HCC (Guo et al, 2011;Kinoshita et al, 2013). In addition, He et al showed that SLC7A11 can up-regulate the expression of PD-L1 and CSF1, and promote the infiltration of TAMs and MDSCs in HCC, as well as the metastasis of HCC (He et al, 2021). STC2 is the target gene of HIF-1 and has been proved to be a prognostic marker of ovarian cancer, breast cancer, and kidney cancer (Chang et al, 2003;Buckanovich et al, 2007;Esseghir et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This αKG- HIF1α cascade upregulates PD-L1 and colony-stimulating factor-1 (CSF1), which further increase HCC metastasis via infiltration of tumor associated macrophages (TAMs) and myeloid derived suppressor cells (MDSCs). Either depletion of TAMs or MDSCs, treatment with a CSF1 inhibitor, an anti-PD-L1 antibody or Anakinra (an IL1β inhibitor), or SLC7A11 knockdown, all result in a reduction in HCC metastasis ( 114 ). xCT inhibition by sulfasalazine or through siRNA targeting SLC7A11 leads to reduced cell proliferation in vitro and in-vivo via reduction in GSH levels and an increase in ROS by inhibiting the CD44v9-SLC7A11 interaction ( 111 , 113 ).…”
Section: Gastrointestinal Tract Cancersmentioning
confidence: 99%